A zebrafish transgenic model of Ewing's sarcoma reveals conserved mediators of EWS-FLI1 tumorigenesis - Stefanie W. Leacock; Audrey N. Basse; Garvin L. Chandler; Anne M. Kirk; Dinesh Rakheja; James F. Amatruda (The Company of Biologists, 2012)
SUMMARY Ewing's sarcoma, a malignant bone tumor of children and young adults, is a member of the small-round-blue-cell tumor family. Ewing's sarcoma family tumors (ESFTs), which include peripheral primitive neuroectodermal tumors (PNETs), are characterized by chromosomal translocations that generate fusions between the EWS gene and ETS-family transcription factors, most commonly FLI1. The EWS-FLI1 fusion oncoprotein represents an attractive therapeutic target for treatment of Ewing's sarcoma. The cell of origin of ESFT and the molecular mechanisms by which EWS-FLI1 mediates tumorigenesis remain unknown, and few animal models of Ewing's sarcoma exist. Here, we report the use of zebrafish as a vertebrate model of EWS-FLI1 function and tumorigenesis. Mosaic expression of the human EWS-FLI1 fusion protein in zebrafish caused the development of tumors with histology strongly resembling that of human Ewing's sarcoma. The incidence of tumors increased in a p53 mutant background, suggesting that the p53 pathway suppresses EWS-FLI1-driven tumorigenesis. Gene expression profiling of the zebrafish tumors defined a set of genes that might be regulated by EWS-FLI1, including the zebrafish ortholog of a crucial EWS-FLI1 target gene in humans. Stable zebrafish transgenic lines expressing EWS-FLI1 under the control of the heat-shock promoter exhibit altered embryonic development and defective convergence and extension, suggesting that EWS-FLI1 interacts with conserved developmental pathways. These results indicate that functional targets of EWS-FLI1 that mediate tumorigenesis are conserved from zebrafish to human and provide a novel context in which to study the function of this fusion oncogene.